Of bears & weight loss : how to manage triggers, lose weight, and enjoy getting fit - King, Brian (Comedian) (Apollo Publishers, 2023)
"Dr. Brian King studied neuroscience and psychology before touring the world as a stand-up comedian and public speaker. Yet despite giving life guidance to others, he was carrying an extra one hundred pounds, taking up too much space in airplane seats and keeping the opposite sex at bay. When Dr. Brian committed to change, he embraced his understanding of human behavior and mindsets to reframe his approach to a healthy lifestyle. Now having lost most of the weight, he uses his signature combination of humor and neuroscience to delve deep into mindfulness, stress, habits, willpower, diet, exercise, and much more to guide readers in losing weight and keeping it off. ...Whether you are looking to shed those final five, the COVID fifteen, or the weight of another adult, Of Bears and Weight Loss offers life-changing tips and instructions that will have you embracing change with humor and the power to finally see your goals through to completion." -- Amazon.com.